Minimally invasive transvaginal single-port laparoscopic vesicovaginal fistula repair: a case report and the point of this technique - Huang, Jianbiao; Cheng, Yu; Wang, Bin; Chao, Haichao; Xu, Xiangda; Zeng, Tao (Frontiers in Surgery, 2024)
The optimal surgical method of vesicovaginal fistula (VVF) remains uncertain. Minimally invasive surgical approaches have become highly popular in line with technological advancements, namely, laparoscopic, robotic, and used. However, these techniques still require invasiveness. This is the first case report that described a novel "zero-incision" technique for natural orifice transvaginal single-port laparoscopy used to repair a recurrent and high-position VVF. The patient underwent transvaginal single-port laparoscopic repair of a VVF. Methylene blue was used to locate the VVF, and a needle electrode was used to thoroughly remove the scar tissue of the VVF. In addition, this technique for transvaginal single-port laparoscopy provides more working space to expose and repair fistulas conveniently and adequately. One year after surgery, the patient remained asymptomatic and had no fistula recurrence.Minimally invasive transvaginal single-port laparoscopy provides a clear surgical field, is safe and feasible. This novel technique has promising as an additional personalized treatment option for VVF repair.